Study on Deformation and Stability of Rock-Like Materials Retaining Structure during Collaborative Construction of Super-Adjacent Underground Project - Hongfu Qu; Lihua Wang; Chunlei Feng; Hualao Wang; Xuan Zhang (Advances in Materials Science and Engineering)
The collaborative construction of undercrossing tunneling of Gongchang Road and the adjacent Metro Line 6 extension station section in Shenzhen is difficult and of high risk. In view of these characteristics, this paper studied the deformation and stability of rock-like material retaining structures in the process of underground engineering collaboration by combining the measured deformation data and the circular slide theory based on the limit equilibrium method. The results show that due to the difference between the supporting systems of rock-like materials on both sides and other reasons, the upper part of the retaining structure and the limited soil in the adjacent area tilt greatly to one side at the same time, and the surface settlement in the limited soil area also increases with the increase of the excavation depth of the foundation pit. On the basis of measured deformation data analysis, the mechanical model for calculating the stability concerning the relationship between the adjacent distance L of the deep foundation pit and the vertical distance D′ between the lowest support of the foundation pit and the bottom of retaining structures was established. Then, the calculation formula for the against basal heave stability covering different adjacent degrees was established. Besides, the applicability of the calculation method was verified by combining it with the actual engineering and related prediction theories, which further proves that the research results have certain theoretical value and engineering significance, and can provide a reference for the rock-like material retaining structures design and stability analysis of similar projects.